Building a European University Consortium: The case of the U!REKA-Network - Christoph Rosenbusch; Mareike Tarazona; Barbara Lämmlein; Claire Gardent; Ainur Berekbulova; Robin Stevens (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2023)
European policy makers encourage close interorganizational collaboration of universities across national systems. The study at hand analyzes this development from the organizational level of specific Higher Education Institutions (HEIs) and their international network. Using a case study approach, we investigated the development and governance of the U!REKA-Network, a group of European Universities of Applied Sciences, founded in 2016. Compared to other organizational networks, university-networks have specific characteristics with regard to their goals (high importance of prestige and normative goals) as well as to internal management (loose coupling) of the participating institutions. Establishing comprehensive and sustainable collaboration is a challenging task that requires a functioning interplay between university management, academic heartland and support structures. Attractive opportunity structures for academics and students as well as an integrated and persuasive communication is needed to foster network participation on a broader scale. Mutual trust is very important for network engagement as well as its sustainability and the study offers some useful insights on this topic. Concerning the appropriateness of different governance modes, the empirical results furthermore indicate that there is a certain need for central administrative structures on the network level in international university networks. – – Die europäischen Entscheidungsträger fördern eine enge interorganisatorische Zusammenarbeit von Hochschulen über nationale Systeme hinweg. In der vorliegenden Studie wird diese Entwicklung auf der organisatorischen Ebene einzelner Hochschulen und ihres internationalen Netzwerks analysiert. Anhand eines Fallstudienansatzes untersuchten wir die Entwicklung und Governance des U!REKA-Netzwerks, einer 2016 gegründeten Gruppe von europäischen Hochschulen für Angewandte Wissenschaften. Im Vergleich zu anderen organisatorischen Netzwerken weisen Hochschulnetzwerke spezifische Merkmale in Bezug auf ihre Ziele (hohe Bedeutung von Prestige und normativen Zielen) sowie auf das interne Management (lose Kopplung) der beteiligten Einrichtungen auf. Die Etablierung umfassender und nachhaltiger Kooperationen ist eine anspruchsvolle Aufgabe, die ein funktionierendes Zusammenspiel von Hochschulmanagement, akademischem Kernbereich und Unterstützungsstrukturen erfordert. Attraktive Gelegenheitsstrukturen für Wissenschaftler und Studierende sowie eine integrierte und überzeugende Kommunikation sind erforderlich, um die Netzwerkbeteiligung auf breiterer Ebene zu fördern. Gegenseitiges Vertrauen ist sehr wichtig für das Engagement in einem Netzwerk und dessen Nachhaltigkeit, und die Studie bietet einige nützliche Erkenntnisse zu 3 diesem Thema. In Bezug auf die Angemessenheit verschiedener Governance-Modi deuten die empirischen Ergebnisse außerdem darauf hin, dass in internationalen Hochschulnetzwerken ein gewisser Bedarf an zentralen Verwaltungsstrukturen auf der Netzwerkebene besteht.
urn:nbn:de:bsz:946-opus4-68823
Keywords: 330